Sarcopenia Is Associated With Hematologic Toxicity During Chemoradiotherapy in Patients With Anal Carcinoma - Martin, Daniel; von der Grün, Jens; Rödel, Claus; Fokas, Emmanouil (Frontiers in Oncology, 2020)
Purpose: Sarcopenia, defined as a loss of muscle mass and quality, has been associated with impaired oncological outcome and treatment toxicities in several malignancies. However, its role in anal squamous cell carcinoma (ASCC) remains less well explored. Methods/Materials: Planning CT scans were used to measure cross-sectional skeletal muscle area (SMA) to calculate the skeletal muscle index (SMI). The association of sarcopenia with clinical and treatment-related parameters, and toxicity was assessed in 114 patients with ASCC that underwent standard 5-Fluorouracil/Mitomycin C chemoradiotherapy (CRT). The prognostic impact of sarcopenia on local relapse-free survival (LRFS), disease-free survival (DFS) and overall survival was examined using a Cox regression analysis. Results: 29 (25.4%) patients had sarcopenia. Patients with sarcopenia had lower baseline hemoglobin levels (p = 0.002), worse Karnofsky Performance Status (p=0.001) lower BMI (p < 0.001) and a significantly lower body surface area (p = 0.03,), and lower incidence of involved lymph nodes (p = 0.03). Regarding acute toxicity, sarcopenia was associated with a significantly higher incidence of ≥ grade 3leukopenia (OR: 3.5; 95% CI: 1.6 – 7.5, p = 0.007) and ≥ grade 3 thrombopenia (OR: 5.1; 95% CI: 1.3 – 21, p = 0.018) after CRT. Despite higher hematologic toxicity in sarcopenic patients, total treatment time was similar between patients with and without sarcopenia (median 44 vs 45 days, p = 0.95). There was no significant prognostic impact of sarcopenia on either LRFS, DFS or OS. Conclusions: This is the largest study to assess the impact of sarcopenia on toxicity and oncological outcome in patients with ASCC. Increased clinician awareness of higher hematological toxicity risk is needed for sarcopenic patients with ASCC undergoing CRT to facilitate closer monitoring of side effects and earlier introduction of supportive measures. Further prospective studies are needed to elucidate the prognostic role and impact of sarcopenia on CRT-related toxicity in ASCC.